2021 Taiwan Stroke Society Guidelines of blood pressure control for ischemic stroke prevention. Issue 6 (10th June 2022) - Chi, Nai-Fang; Chung, Chih-Ping; Cheng, Hao-Ming; Liu, Chi-Hung; Lin, Chun-Jen; Hsu, Li-Chi; Tang, Sung-Chun; Lee, Jiunn-Tay; Po, Helen L.; Jeng, Jiann-Shing; Wang, Tzung-Dau; Lee, I-Hui; et al.
Abstract : Background: Since the publication of the 2015 Taiwan Stroke Society Blood Pressure for Treatment and Prevention of Stroke Guideline (2015 TSS BP Guideline), several new clinical studies have addressed whether a stricter blood pressure (BP) target would be effective for stroke prevention. Methods: TSS guideline consensus group provides recommendations on BP targets for stroke prevention based on updated evidences. Results: The present guideline covers five topics: (1) diagnosis of hypertension; (2) BP control and primary prevention of ischemic stroke; (3) BP control and secondary prevention of ischemic stroke; (4) BP control and secondary prevention of large artery atherosclerosis ischemic stroke; and (5) BP control and secondary prevention of small vessel occlusion ischemic stroke. Conclusion: The BP target for most stroke patients with hypertension is <130/80 mm Hg.